2017
DOI: 10.1002/jso.24604
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the limits of resectability: Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) using monosegment 6, facilitated by an inferior right hepatic vein

Abstract: We describe our technique using the combination of a recent surgical technique (ALPPS) and an anomalous vascular anatomy to push the current limits of liver resectability. The approach allowed the resection of the three hepatic veins and preserved a peripheral segment 6 as the only future liver remnant, having an inferior hepatic vein as its outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…These data intrigued a growing interest in ALPPS as a new and curative surgical treatment option also in patients with extensive colorectal hepatic tumor burden. Median hypertrophy rates of 160% (range 93–250%) in selected cases even permitted resections of all but one liver segment, the so-called monosegment ALPPS [28, 29]. In 2015, Schadde et al [29] reported 12 cases of “monosegment ALPPS” without any postoperative mortality.…”
mentioning
confidence: 99%
“…These data intrigued a growing interest in ALPPS as a new and curative surgical treatment option also in patients with extensive colorectal hepatic tumor burden. Median hypertrophy rates of 160% (range 93–250%) in selected cases even permitted resections of all but one liver segment, the so-called monosegment ALPPS [28, 29]. In 2015, Schadde et al [29] reported 12 cases of “monosegment ALPPS” without any postoperative mortality.…”
mentioning
confidence: 99%
“…Of 12 patients studied in a case series [ 18 , 57 , 64 68 ] and hospital series [ 59 ] (Table 2 ), 7 were female and 5 were male. Median tumor size was 13.5 cm (range: 7–18 cm), and the median age of the patients was 61.5 years (range: 46–72 years).…”
Section: Resultsmentioning
confidence: 99%
“…The right accessory hepatic vein, present in 30% of patients, provides substantial parenchymal drainage and is often the main source of outflow for segments 6 and 7. 20 Thus, identification of anatomic variants is critical for preoperative planning. 18 In this case, potentially curative resection was dependent on its preservation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar case was reported describing the use of ALPPS with cholangiocarcinoma that encompassed all hepatic outflow except for the right accessory hepatic vein, which was ultimately sufficient to preserve outflow in a monosegmental liver remnant. 20 Thus, identification of anatomic variants is critical for preoperative planning.…”
Section: Discussionmentioning
confidence: 99%